The The Efficiency of Google Classroom during Pandemic for Maritime English Learning in Akademi Maritim Nusantara - Yoana Gita Pradnya Lengari (Saintara: Jurnal Ilmiah Ilmu-Ilmu Maritim, 2021)
For almost 2 years, the educational system around the world has been influenced by the COVID-19 pandemic that leads to the shutting down of educational institutions including universities to control the spreading of the virus. This phenomenon coerces the government and also educational institutions to adapt their learning and teaching process. Along with various policies to handle the situation, the online learning system is suggested by Indonesian government as one of the solutions to facilitate distance learning. One of the methods to conduct distance learning is by using Google Classroom. This is a descriptive qualitative research with the fourth semester Engineering students of Akademi Maritim Nusantara as the subject. The key purpose of this research is to determine the efficiency of Google Classroom in Maritime English subject. The data are analyzed with Technology Acceptance Model (TAM). The efficiency of the platform is measured with the Ease of Access (PEU) and Perceived Usefulness (PU) towards Google Classroom Maritime English learning activity. The result of this study shows that most of the students are satisfied with Google Classroom that is applied in their class during COVID-19 pandemic in terms of the easiness of accessing their assignments, hence their efficiency as a learning tool can be considered appropriate.